TWO CYCLES OF TPF AS INDUCTION CHEMOTHERAPY IN LOCALLY ADVANCED HEAD-AND-NECK SQUAMOUS CELL CANCER FOR INDIAN PATIENTS: CAN LESS BE MORE? - ANVITA BHATI,; RAMESH PUROHIT,; AJAY KUMAR YADAV,; SHASHANK KOTHARI, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: India has a high prevalence of locally advanced head-and-neck (H&N) cancer, with poor outcomes from concurrent chemoradiotherapy (CRT). Many centers widely practice induction chemotherapy (IC) to address this. The commonly used IC regimen with three cycles of docetaxel, cisplatin, and 5-fluorouracil (TPF) often results in poor tolerance and low compliance among Indian patients. This single arm study assess the efficacy, toxicity, and compliance of two cycles of TPF as IC followed by CRT in locally advanced H&N cancers. Methods: We enrolled adult patients with previously untreated, non-metastatic, newly diagnosed, unresectable, and locally advanced H&N cancer planned for definitive CRT in tumor board. Patients were scheduled for IC with two cycles of TPF followed by concurrent CRT with weekly cisplatin. Results: Between October 2022 and March 2024, we enrolled a total of 58 patients for the study. After two cycles of IC, 11 patients defaulted, and three had progressive disease. Out of the 44 patients who started CRT, 32 completed the treatment. Three patients were lost to follow-up. We observed a complete response in 27 patients (84.3%). Only two patients had residual disease, and no distant failures occurred. The treatment was well tolerated, with no cases of neutropenia. We noted grade 2 neutropenia in one patient during IC and 11 patients during CRT. Grade 3 mucositis appeared in 5 patients (15.6%) and Grade 3 dysphagia in 7 patients (21.9%). Conclusion: Two cycles of TPF IC demonstrate good tolerance and efficacy, making them a viable option for sequential treatment of locally advanced H&N cancers in Indian settings.